Uterine myxoid leiomyosarcoma: a diagnostic challenge - Durairaj, Jayalakshmi; Chandrasekaran, Swaramya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine sarcomas are histologically diverse tumours which comprise about 3-7% of uterine malignancies. Myxoid leiomyosarcoma (MLMS) is an extremely uncommon variant of uterine leiomyosarcoma. This report is of a 35 year old woman who presented with urinary retention and abnormal vaginal bleeding, who underwent a total abdominal hysterectomy for cervical fibroid. A diagnosis of leiomyoma with myxomatous degeneration was made. The woman subsequently developed a recurrence within 5 months of the surgery and was diagnosed with MLMS following biopsy. This case reiterates the uncertainties associated with the diagnosis of MLMS and the need for heightened vigilance in women with myxomatous degeneration of leiomyoma.